The “Pluma”: Corporalities That Challenge the Normativity in School Settings [a “Pluma”: Corporalidades Que Desafiam a Normatividade No Ambiente Escolar] [la “Pluma”: Emplazamientos de Cuerpos Que Interpelan la Normatividad en Escenarios Escolares] - Contreras-Salinas, S (State Univ of Rio de Janeiro - Center of Childhood and Philosophy Studies, 2020)
The purpose of this article is to interpret some selections from the narratives of LGBT subjects (Lesbians, Gays, transsexuals and Bisexuals) in relation to the corporality expressed in the school settings. The narratives that were produced over the course of 2012-2013, and our focus on corporality is one of many that allude to the binary classification and separation of sex-gender construct, man / woman and masculine / feminine, in this case, reproduced by subjects whose forms and desires do not conform to the established ones. This trope referred to in the narratives allows us to reveal both the gender constructions of LGBT subjects, as well as the experiences of themselves that occur in circumstances in which difference and visibility are repressed and subalternized by a normalizing pedagogical practice. The "pen" is an unwanted or unexpected irruption, which obtains as a response to homo / lesbo / bi / trans phobic practices that emerge to hurt anyone who dares to appear in front of others in their difference or from a divergent position. This trope would appear be one of the many that allude to the classification and binary separation of sex-gender, man / woman, male / female, in this case, reproduced by subjects whose forms and desires do not conform to established conventioins. As such it can be seen in the narratives that the presence of the pen is not completely transparent, and creates lacunae and contradictions, in addition to persisting in its resistance to recognizing the diversity of bodily materializations. © 2020 State Univ of Rio de Janeiro - Center of Childhood and Philosophy Studies. All rights reserved.